Analytical modelling solution of producer mobility support scheme for named data networking - Muktar Hussaini; Shahrudin Awang Nor; Amran Ahmad (Institute of Advanced Engineering and Science, 2019)
Named Data Networking (NDN) is a clean-slate future Internet architecture proposed to support content mobility. However, content producer mobility is not supported fundamentally and faces many challenges such as, high handoff latency, signaling overhead cost and unnecessary Interest packet losses. Hence, many approaches indirection-based approach, mapping-based approach, locator-based approach and control/data plane-based approach were proposed to address these problems. Mapping-based and control/data plane-based approach deployed servers for name resolution serveces to provide optimal data path after handoff, but introduces high handoff latency and signalling overhead cost. Indirection-based and locator-based approach schemes provide normal handoff delay, but introduces sub-optimal or tiangular routing path. Therefore, there is needs to provide substantial producer mobility support that minimizes the handoff latency, signaling cost and improve data packets delivery via optimal path once a content producer relocates to new location. This paper proposed a scheme that provides optimal data path using mobility Interest packets and broadcasting strategy. Analytical investigation result shows that our proposed scheme outperforms existing approaches in terms of handoff latency, signaling cost and path optimization.